Strategies for Using the Sheep Ovarian Cortex as a Model in Reproductive Medicine - Fransolet, Maïté (Public Library of Science, 2014)
OBJECTIVE: To evaluate and compare the distribution and density of primordial follicles within a whole sheep ovary and to gain insight into how to overcome the impact of natural follicular heterogeneity on the experimental results. DESIGN: Histological study. SETTING: Academic research center. ANIMALS: Five- to nine-month-old ewes. INTERVENTIONS: Freshly sampled whole sheep ovaries were collected and prepared for histological analysis. MAIN OUTCOME MEASURE(S): The follicular densities and distributions were determined for hematoxylin and eosin sections. A mathematical model was derived based on the follicle counts and Monte-Carlo simulations. RESULTS: Heterogeneous distributions and densities of primordial follicles were identified 1) for distinct areas of the same ovarian cortex, 2) between the ovaries of the same animal and 3) across different ewes. A mathematical model based on the analysis of 37,153 primordial follicles from 8 different ovaries facilitated the estimation of the number of cortical biopsies and sections that had to be analyzed to overcome such heterogeneity. CONCLUSION: The influence of physiological follicular heterogeneity on experimental and clinical results can be overcome when a definite number of cortical pieces and sections are taken into consideration.